Infrared light stimulates the cochlea through a mechanical displacement detected and amplified by hair cells - Julien B. Azimzadeh; Patricia M. Quiñones; John S. Oghalai; Anthony J. Ricci (Proceedings of the National Academy of Sciences, 2025)
Although cochlear implants (CI) are the standard of care for profound sensorineural hearing loss they are technically constrained by the tendency of electrical current to spread within the fluid-filled chambers of the cochlea. This limits the resolution of individual electrodes and patients’ perceptions of complex sounds. Infrared irradiation has been proposed as an alternative to electrical stimulation because it can elicit auditory responses while being spatially constrained, theoretically promising higher-fidelity hearing for the deaf. However, conflicting reports locate the site of infrared excitation at spiral ganglia neurons or hair cells. We use a combination of genetic, pharmacological, optical, and electrophysiological tools to determine the site of action of infrared irradiation. Infrared-evoked cochlear potentials are composed of two peaks: one driven by hair cells (the microphonic) and a second driven by spiral ganglion neurons (the neural response). Manipulations that prevented hair cell synaptic activity abolished the neural component, while manipulations blocking hair cell mechanotransduction abolished all responses, suggesting a mechanical component to the infrared response. Optical coherence tomography (OCT) confirmed that infrared irradiation creates a mechanical stimulus that is both amplified and detected by hair cells. Because infrared irradiation does not stimulate spiral ganglion neurons directly, it is unlikely to replace the electrical CI.